Mechanical properties of a bioabsorbable magnesium interference screw for anterior cruciate ligament reconstruction in various testing bone materials - Nad Siroros; Ricarda Merfort; Yu Liu; Maximilian Praster; Filippo Migliorini; Nicola Maffulli; Roman Michalik; Frank Hildebrand; Jörg Eschweiler (Scientific Reports, 2023)
Abstract Tears of the anterior cruciate ligament (ACL) negatively impact the stability and kinematics of the knee. Interference screws (ISs) are used for graft fixation in ACL reconstruction and provide sufficient fixation strength to withstand the patients' activities during the graft-to-bone integration process. Magnesium is a novel material used to manufacture IS given its strength and bioabsorbability. In previous studies, the selected magnesium IS design showed a better fixation performance in comparison to the conventional IS design due to its shape design and surface condition. In this study, bioabsorbable magnesium ISs were tested for their insertion (insertion torque and a number of turns to implement the IS) and fixation performance (pull-out and dynamic test). To obtain a reliable initial assessment of IS performance, ISs were implanted in 15 per cubic foot (PCF) Sawbones polyurethane foam blocks, Sawbones biomechanical tibia models with 17 PCF foam cores, and human cadaveric tibiae. Porcine tendons were used in the foam block pull-out test, and nylon ropes were used in all other test setups to prevent influences of the ligament graft material itself. In the pull-out test, the graft was subjected to tensile stress at a rate of 6 mm/min. For the dynamic test, 1000 cycles between 0 and 200 N were performed, followed by a final pull-out test. After each test, the tunnel widening pattern was observed by measuring the aspect ratio of the tunnel at the insertion site. The insertion torque lies within the normal insertion torque of the ISs as well as the average ligament tension before the insertion. In the foam block setup, the nylon rope showed a higher pull-out force than the porcine tendon. The comparison of each setup using nylon rope for both pull-out and pull-out after the dynamic test showed no significant difference between the foam block and cadaver setup. However, all tibia model setup shows unexpectedly high pull-out force due to the influence of its cortical layer. There were no statistically significant differences in tunnel widening between foam block-porcine tendon and foam block-nylon rope constructs. The pull-out resistance of magnesium ISs falls within the typical ACL tension range during daily activities. Even though the test results of the magnesium ISs are different in each bone material, the magnesium IS shows adequate fixation ability and workability during insertion without material failure.